(untitled) (Acta Polytechnica CTU Proceedings, 2017)
Crosswalk is an essential element of the transport system of any city. A priority assignment in any such crossing is to ensure the safety of pedestrians. Underground pedestrian crossings are much safer than crossings at another level, but they lose in attraction when it comes to cost. The cost of the construction of an underground pedestrian crossing often leads to project abandonment. The cost of construction can be reduced through the use of flexible corrugated metal structures instead of ordinary concrete structures. The stress-strain state of the structural shells need to be known to facilitate their rational design. The stress-strain state of flexible corrugated metal shells largely depends on the strength and deformation characteristics of the surrounding soil. Therefore, improving the characteristics of backfill soil is an urgent task in reducing the cost of construction for such tunnels. One way to improve the strength and deformation characteristics of soils is the use of reinforcement. Currently, there are a large number of reinforcement schemes and also associated reinforcing materials. One of the most prospective methods of soil reinforcement is the use of fibre filaments. Fibre reinforced soils have significantly higher strength and deformation characteristics in comparison with unreinforced soils. Numerical modelling of a tunnel shell made out of a corrugated metal structure was undertaken to evaluate the effectiveness of using fibre reinforced sand. Ordinary sand and sand reinforced with polypropylene fibres have been used as soil backfill. The calculation results for a pedestrian tunnel structure involving different strength and deformation characteristics of the backfill soil are presented in this article.